2012
DOI: 10.3389/fonc.2012.00148
|View full text |Cite
|
Sign up to set email alerts
|

Generation of polycyclic aromatic hydrocarbons (PAHs) during woodworking operations

Abstract: Occupational exposures to wood dust have been associated with an elevated risk of sinonasal cancer (SNC). Wood dust is recognized as a human carcinogen but the specific cancer causative agent remains unknown. One possible explanation is a co-exposure to; wood dust and polycyclic aromatic hydrocarbons (PAHs). PAHs could be generated during incomplete combustion of wood due to heat created by use of power tools. To determine if PAHs are generated from wood during common wood working operations, PAH concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…When wood workers manipulate wood melamine using power tools, PAHs are generated as shown in our previous study. 16 Total PAH concentrations decreased in the following order of wood dust collected after use of different power tools under controlled conditions: wood melamine . oak .…”
Section: Discussionmentioning
confidence: 98%
“…When wood workers manipulate wood melamine using power tools, PAHs are generated as shown in our previous study. 16 Total PAH concentrations decreased in the following order of wood dust collected after use of different power tools under controlled conditions: wood melamine . oak .…”
Section: Discussionmentioning
confidence: 98%
“…The International Agency for Research on Cancer has classified wood dust as carcinogenic to humans based on the strong associations between SNC and wood dust exposures identified in several epidemiological studies (Group 1) (10). Wood dust particles generated during woodworking operations are composed mainly of largest particles (>10 µm) (11)(12)(13). Largest wood particles are known to deposit in the sino-nasal region, making the nose the target organ (14).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PAH load in road dust in Surfers Paradise is lower than in Benowa. The high load of PAHs in road dust in Nerang is attributed to the numerous industrial activities such as painting, timber processing and furniture manufacturing in the area which can generate significant PAH loads (Dong and Lee, 2009;Wang et al, 2011;Bruschweiler et al, 2012;Kho et al, 2014). These results suggested that since areas with vehicle related business activities, high traffic volume and industrial activities can lead to high PAH loads and hence could pose higher risks.…”
Section: Analysis Of Pahs On Urban Roads In Gold Coastmentioning
confidence: 98%